Perencanaan Sistem Plambing Air Buangan Gedung Rusunawa Mahasiswa Universitas Andalas - Puti Sri Komala; Suarni S. Abuzar; Purnama Mentari Dewi (Fakultas Teknik, 2019)
According to Indonesian National Standard (SNI) No.03-7065-2005, the building with more than 500 inhabitants, should prepare plumbing system design. The plumbing sewerage design of student flats building referred to SNI 03-6481- 2000 and SNI 03-7065-2005. Sewerage system for black- and grey water was discharged separately. Black water comes from the closet and the toilet clean out, while grey water comes from the lavatory, sink and floor drain. The wastewater flow rate is determined based on the plumbing fixtures. The sewage flowed partially full in horizontal pipe, and discharged into the standpipe in the the building shaft then flowed to the wastewater treatment plant i.e anaerobic-aerobic bioseptic tank. Grease traps are mounted at the sink to separate oils and fats. Each wastewater fixture is equipped with a fixture vent connected to the standpipe vent which extended through the roof to outdoors. Vent system consists of the vent circuit that connected to the toilet and the floor drain respectively, and the single vent that connected to the sink and the lavatory respectively. Black water sewerage pipes used 3-4 inches PVC, while the grey water sewerages used 1 ½ - 2 ½ inches PVC, and vent used pipe 2-4 inches PVC.